Exploring firefighters perceptions of how their working experience and personal lives influence each other - Metcalf, Nicolette (Department of Social Development, 2021)
The aim of this qualitative study was to explore firefighters' perceptions of how their working experiences and personal lives positively and negatively influence each other. The purpose of this study was also to understand firefighters' perceptions of the support that is currently available to them and what further support they require, in order to cope with the demands of work and personal relationships. The research was conducted in two research settings and permission was gained to conduct the research from the City of Cape Town's Research Department and the Fire Chief of the Fire and Rescue Department. A qualitative research design was used to conduct this study, and purposive sampling was used to select the sample. A total of twenty, male firefighters were interviewed using a semi-structured interview schedule. A digital recorder was used to ensure that the interviews could be recorded accurately. The interviews were transcribed and analysed following Tesch's (1990) method of data analysis. The findings from this study reflect that the participants' work experiences and personal lives do influence each other. The participants reported that the training and education they received to become a firefighter, their relationship with their colleagues, and shift work had a positive influence on their personal lives. At the same time a number of workplace stressors such as shift work, repeated exposure to trauma, challenging aspects of career advancement and the negative consequences of the rank structure, were identified as negatively influencing their personal lives. Positive factors such as social support including support from family and work as well as religious support help buffer the negative effects of stress experienced by firefighters in their work. Personal and family challenges were seen to have a negative influence on firefighters working experience. Lastly, recommendations were made to various stakeholders including the Fire and Rescue Department as well as the Employee Assistance Programme (EAP) and Wellness branch. These included the need for online surveys, sports days and informal meetings between management and firefighters. Recommendations to EAP and Wellness branch included 2 continuous marketing of EAP services, pro-active interventions such as stress management and building resilience for firefighters, management training as well as wellness events.